Experimental Characterization of Bacterial Concrete Against Mechanical and Durability Performance - Buller, A. S.; Buller, A .M.; Ali, T.; Tunio, Z. A.; Shabbir, S.; Malik, M. A. (Engineering, Technology & Applied Science Research, 2021)
This study experimentally investigates the mechanical and durability performance of bacteria concrete in terms of density, compressive strength, split tensile strength, and water absorption capacity. The concrete specimens were produced with a ratio of 1:2:4, w/c ratio of 0.45, and having a bacteria dosage level ranging from 1 to 6% by weight of water. To investigate the usefulness of the bacteria dosage level, cubic and cylindrical specimens were cast and tested after 28 days of water curing in a Universal Testing Machine with a constant loading rate. The density of each specimen was also recorded soon after casting and after the curing period ended. Moreover, the water absorption test was similarly conducted on cube specimens at various time intervals to record the penetration depth. The test results of normal concrete (without bacteria) were compared with the ones of the specimens containing bacteria. The optimum level of bacteria was found to be 3.5%, which showed the highest values in terms of compressive strength, split tensile strength, and density. Bacteria tend to generate more crystalline materials inside the concrete mass due to reactions with the surrounding moisture which produces a compact surface, thus strength properties were improved and water penetration was blocked which suggests better durability of the concrete.